(untitled) (Stavební obzor - Civil Engineering Journal, 2024)
The reinforced concrete structure is the most widely used structural form today. In the western salt-alkali areas and in road and bridge projects in the northern regions where de-icing agents are applied, chloride ion intrusion into concrete leads to rebar depassivation and corrosion. With the occurrence and intensification of corrosion, the expansion of corrosion products leads to cracking or spalling of the concrete cover, resulting in durability damage to the reinforced concrete structure. Among all the components of the bridge, the bridge deck panels suffer the most severe and direct damage from salt freezing. Therefore, predicting the service life under salt freezing conditions is an urgent issue to address for the durability design, evaluation, and structural maintenance decision-making for reinforced concrete bridge deck panels.